Laboratory assembly of the Civil Construction Area: Experience Report from the teaching-learning outline (Research, Society and Development, 2021)
Teaching in the field of Civil Construction in Brazil has pedagogical bases that, in most cases, do not directly link the student to real situations in the society in which they are immersed. Thus, it is very common to naturally enhance theoretical teaching dissociated from practice, sometimes due to the time it takes to complete the curriculum, sometimes due to the complexity of the content itself. However, this naturalness of theoretical teaching has hindered the training of some professionals who arrive in the job market without a real sense of the development of a work and the connection of its parts. Therefore, the interdisciplinarity between the construction stages and the use of laboratories for real test simulations can add to the improvement of the teaching-learning process. This study brings, from an experience report, the process of setting up a laboratory in the area of Civil Construction (Constructive Techniques) on a campus of the Federal Institute's network in Brazil, considering critical analyzes on the favor of teaching and learning in spaces like this. Methodological steps were followed that could present challenges and rewards in the insistence of setting up this laboratory; such as, for example, the gradual rescue of the process of practical teaching in the area of civil construction on this campus, a natural appropriation of space by the academic community and the beginning of the awareness that the education process exists to propagate and improve knowledge to improve society in which it is inserted.